CHOCOLATE BAR WITH MORINGA AND DATES AS CALCIUM-RICH FOOD WITH LOW GLYCEMIC INDEX FOR ENDURANCE ATHLETES - Patmawati, Ini (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2020)
This research aims to provide chocolate for endurance athletes by utilizing the potential of highly nutritious local foods. The ingredients used are chocolate, moringa leaves (Moringa oleifera), and dates (Phoenix dactylifera). This research method uses a Completely Randomized Design (CRD) with One Way Anova statistical analysis. Samples were analyzed by testing in a food laboratory. In this study, moringa powder was used for its calcium content and dates were used for its carbohydrates content with a low glycemic index. In 100 grams of developed chocolate contains 3.27 g of water, 1.83 g of ash, 30.4 g of fat, 5.32 g of protein, 59.1 g of carbohydrate, 0.38 g of crude fiber, 427.07 mg of calcium.